High Resolution Sheet Resistance Mapping to Unveil Edge Effects in Industrial IBC Solar Cells. (August 2016) - Spinelli, Pierpaolo; Danzl, Pi; Guillevin, Nicolas; Mewe, Agnes; Sawallich, Simon; Vlooswijk, Ard; van de Loo, Bas; Kessels, Erwin; Nagel, Michael; Cesar, Ilkay
Abstract: We present Terahertz (THz) transmission measurements with a spatial resolution of down to 10 μm as a new inspection technique for high-resolution sheet resistance ( R sh ) measurements, that are well suited to quantify the local R sh (n-type and p-type regions) of interdigitated back-contact (IBC) structures and to support further optimization of our IBC cells. Using this technique, we investigated the homogeneity of the emitter of our IBC cells. We have greatly improved the R sh homogeneity of the boron diffusion. Moreover, we compared THz mapping with standard four point probe (4pp) technique. While the 4pp measurement showed a homogeneous mapping, the THz could unveil elevated R sh near the very edge of the wafer. Higher R sh of the surface doping can result in higher J 0 at the metal contact regions ( J 0, contact ). A local V oc mapping technique was used and it was found that the local V oc at the wafer edge was lowered by 17 mV compared to the centre in the most extreme case. We estimate that an improved edge doping could result in a performance gain of at least 0.2% absolute, excluding FF and Jsc benefits. In summary we show that THz mapping is a powerful method in determining inhomogeneities and can aid in the development of diffused-junction IBC solar cells.